Infection-related mortality and infection control practices in childhood acute myeloid leukemia in a limited resource setting: Experience with the Indonesian national protocol - Supriyadi, Eddy; Purwanto, Ignatius; Widiastuti, Zeni; Armytasari, Inggar; Sandi, Salsabila; Ardianto, Bambang; Kaspers, Gertjan J. L. (Belitung Raya Foundation, Indonesia, 2024)
Background: In resource-limited settings, addressing infections remains a substantial challenge in the management of children with Acute Myeloid Leukemia (AML). In Indonesia, infection-related mortality (IRM) is thought to be high compared to high-income countries. However, there has been no previous study of infection profile and IRM in Indonesian patients with AML. Objective: This study aimed to describe infections and IRM in children with AML treated according to the Indonesian National AML protocol and to describe the implementation of infection control practices in resource-limited settings. Methods: This retrospective observational study used secondary data from the medical records of pediatric patients with AML treated with the National Protocol at Dr. Sardjito Hospital, Yogyakarta, Indonesia, from April 2012 to September 2018. Essential patient characteristics, time of IRM, and cause of death were recorded, and infection control practices were observed. Data were analyzed using descriptive statistics. Results: 113 patients with AML were treated with the National protocol, and 83 met the inclusion criteria. Infections occurred in 69 (83%) patients with a total of 123 episodes (mean 1.8/patient). Death was seen in 48 (58%) patients, with 19 (23%) IRM. The majority of infections were in the gastrointestinal tract (n = 51, 30.5%), sepsis (n = 29, 17%), and respiratory tract (n = 28, 17%). Infections mostly occurred during the first induction (41%). There were 90 (73%) episodes of clinically documented infection and 33 (27%) episodes of microbiologically documented infection. The positivity rate of blood cultures was only 27%. The majority of bacteria detected were gram-negative (n = 25, 69%), and among them were Klebsiella pneumonia (19%) and Escherichia coli (19%). Candida albicans was detected in 1 (2%) culture. Suboptimal infection prevention and control were found in the clinical practice. Conclusion: Infections and infection-related mortality in children with AML treated using the National protocol were frequent, mainly occurring during the first induction phase. Compliance with infection prevention and control measures needs improvement. Urgent attention is required for better supportive care, including isolation rooms, antibiotics, and antifungals. The predominance of Gram-negative bacterial infections highlights the necessity for further research into effective prophylaxis. Enhanced healthcare and nursing professional vigilance and tailored antibiotic strategies are vital. Improving compliance and ensuring adequate supportive care resources are essential, emphasizing nursing’s pivotal role. Further research is crucial to drive advancements in infection control strategies.